Electrochemical degradation of the dye reactive orange 16 using electrochemical flow-cell - Gomes,Luciano (2011)
Electrochemical removals of color and organic load from solutions containing the dye reactive orange 16 (RO16) were performed in an electrochemical flow-cell, using a platinum working electrode. The influence of the process variables flow-rate, such as NaCl concentration, applied potential and solution pH, were studied. The best color removal achieved was 93% (λ = 493 nm) after 60 min at 2.2 V vs. RHE electrolysis, using 1.00 g L-1 NaCl as supporting electrolyte. The rises in the concentration of NaCl and applied potential increased the color removal rate. The best total organic carbon removal (57%) was obtained at 1.8 V, without the separating membrane, indicating that the ideal conditions for the color removal are not necessarily the same as those to remove the total organic carbon. The degradation efficiency decreased with the solution pH decrease.